Biological Characteristics Analysis of Limosilactobacillus reuteri JBR3 and the Effect of Protective Agents on Its Viability - Jun HAN; Yi WANG; Kaiping ZHANG; Jianjun TIAN (Shipin gongye ke-ji)
In order to advance the application of Limosilactobacillus reuteri IMAUJBR3 in meat fermenters, the strain was subjected to comprehensive genomic, metabolic and biological analyses. Additionally, one-way and response surface experiments were conducted to identify the optimal ratio of protectants for freeze-drying of lactic acid bacteria. The genome of JBR3 was found to consist of one circular chromosome and two circular plasmids. Five sterol esterase-producing enzyme (EC 3.1.1.13) genes, including gene0325 and gene1042, were identified in the metabolic system, which could be hydrolysed to produce sterols and fatty acids. In the probiotic characterisation, no biogenic amine-related genes were annotated. However, several chaperonin genes, such as groEL and groES, and cold stress genes, gene0733 and gene1677 were found. The presence of these genes ensured that the functional properties of the strain could be maintained during the period of cold stress in lactic acid bacteria. This suggested that the strain was suitable for freeze-drying. In addition, JBR3 contained an intact NADH system, yfeX peroxidase, gor glutathione reductase, trxA thioredoxin and trxB thioredoxin reductase. This suggested that JBR3 might have a superior antioxidant capacity, which could be exploited as a fermentation agent in fermented foods. JBR3 was freeze-dried under a protective agent complex of skimmed milk powder (9.3 g/100 mL), maltodextrin (2.3 g/100 mL), monosodium glutamate (6.8 g/100 mL), and trehalose (10.0 g/100 mL). The survival rate of the strain was 95.17%±0.57%, with a viable bacterial number of 9.20×1010 CFU/g. The strain has a promising future in various applications.